Aigai, Türkei. NekroPergEol – Oberflächenuntersuchungen in den Nekropolen der aiolischen Polis Aigai. Die Arbeiten des Jahres 2016 - Kelp, Ute (e-Forschungsberichte des DAI, 2017)
The necropoleis and the great tumuli of Pergamon and the Aeolian cities represent a valuable archaeological heritage for understanding the political, social and cultural dynamics in a key region of Hellenistic Asia Minor. Aiming to enhance their research in funerary archaeology a three-year collaborative French-German programme was created (NekroPergEol). In 2016, the fieldwork lasted one month and was focussed on the intensive survey in the necropolis of the Aeolian city of Aigai. The French-German-Turkish-Italian team documented the peri-urban areas (about 40 %) of the main Northeast necropolis and worked on the necropolis findings of the excavations in 2005 and 2015.